No Structural Change in Mice Intestinal Gut-Associated Lymphoid Tissue After Trichuris muris Egg Infestation - Illiandri, Oski (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2021)
Introduction: It has been known that the infestation of Trichuris muris egg in the intestinal mice may induce a host immune ‎response to eliminate the worms. Worms antigen will stimulate host immune response in the intestinal ‎secondary lymphoid organs. One of the secondary lymphoid organs in the intestinum is GALT (gut-‎associated lymphoid tissue). Worm antigen activate naive T cells and naive B cells in GALT and ‎trigger differentiation of T cells into Th2 and stimulate B cell to produce gut IgE. However a structural change of GALT structure is still poorly understood.‎ Objective: This study aims to find influence of embrionic Trichuris muris egg infestation to the structural ‎changes of mice intestinum GALT.Methods: This research uses true experimental method with post-test only with control group design. Mice are grouped into 3 groups. The first group was given 40 Trichuris muris embryonic egg peroral, second group was given 200 eggs, and third was control group. On the 30th day after treatment, the mice were sacrificed and intestinal GALT structural change has been analyzed (p<0.05). Results: There was no effect of Trichuris muris embryonic egg infestation on the structure of mice intestinum GALT. However, there is a unique finding of GALT in the form of a Peyer’s patch in the basal plica transversalis colon proximalis of 1 mice given egg T. peroral murmus, at low doses or high doses. Conclusion: There was no effect of Trichuris muris embryonic egg infestation on the structure of mice intestinum GALT